Strengthening of Garudchatti bridge after failure of Chauras bridge. (April 2016) - Birajdar, Harshad Subhashrao; Maiti, Pabitra Ranjan; Singh, Pramod Kumar
Abstract: Two continuous lattice steel truss bridges spanning 190 m with subdivided top chord members were constructed on the same design across river Alaknanda at Dugadda and Srinagar, respectively, in Uttarakhand, India. Both bridges were similar in design and geometry having middle span of 110.0 m and two end spans of 40.0 m. Garudchatti bridge at Dugadda was constructed first and opened to traffic, but excessive vibrations and lifting of end supports under live load condition were observed. Construction of Chauras bridge at Srinagar started later, but it collapsed during casting of the deck slab due to buckling of one of its top chord compression members. Failure of Chauras bridge led to the serious concerns in the minds of people and technocrats about the safety of Garudchatti bridge also, because it was constructed using the same design of Chauras bridge. Therefore, it was decided to strengthen and carry out load testing of Garudchatti bridge before reopening to the traffic. In the present work analyses of Garudchatti bridge are presented to identify structurally unsafe members for most severe live loads given in IRC:6-2010 code, and recommendations for strengthening of the critical members. Finite element space frame analyses of the bridge were carried out using STAAD Pro. v8i software to find excessively stressed members beyond their permissible stress limit. The critical compression members were strengthened by welding additional channel sections. RCC anchor blocks were constructed to restrict lifting of end supports under live load. After strengthening, load testing of the bridge was performed to ensure the safety of the bridge. The bridge is now reopened for traffic. In the past a number of bridges have collapsed during load testing. In case of any shortcoming in the design or overloading during load testing, compression members of the truss may suddenly buckle and cause collapse of the bridge. Therefore, it is not advisable to load test steel truss bridges which do not have adequate margin beyond the service load condition. Highlights: Collapse of Chauras bridge and success of Garudchatti bridge on the same design are presented. Buckling of one of the top chord members of Chauras bridge steel truss caused failure. Bridge design is recommended to be checked at the Limit State of Strength also. Before load testing of a bridge sufficient reserve strength must be insured.